2019
DOI: 10.1186/s40594-019-0187-y
|View full text |Cite
|
Sign up to set email alerts
|

Splits in students’ beliefs about learning classical and quantum physics

Abstract: Background: While there has been increasing recognition of the importance of attending to students' views about what counts as knowing and learning a STEM field, surveys that measure these "epistemological" beliefs are often used in ways that implicitly assume the fields, e.g., "physics," to be a single domain about which students might have sophisticated or naïve beliefs. We demonstrate this is not necessarily the case and argue for attending to possible differences in students' epistemological beliefs across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…As such, these instruments do not provide a description of student epistemology per se; rather, they assess student alignments with already established, dominant ways of thinking in the sciences. Dreyfus et al (2019) note that a similar phenomenon has occurred in the field of physics, but they argue that there are no single domains of knowledge that determine a sophisticated/naive dichotomy within the field.…”
Section: A Need For Epistemological Diversity In Stemmentioning
confidence: 94%
“…As such, these instruments do not provide a description of student epistemology per se; rather, they assess student alignments with already established, dominant ways of thinking in the sciences. Dreyfus et al (2019) note that a similar phenomenon has occurred in the field of physics, but they argue that there are no single domains of knowledge that determine a sophisticated/naive dichotomy within the field.…”
Section: A Need For Epistemological Diversity In Stemmentioning
confidence: 94%
“…So, in this segment, we see Fred invoking an epistemological view about quantum mechanics-"[it] doesn't make sense a lot of the time"-as a warrant for dismissing their physical intuition when it conflicts with their counterintuitive equation-based conclusion. While this attitude is sometimes expressed by introductory students about physics in general, it is also exhibited in ways specific to quantum mechanics even among more advanced students and experts [4,44,45]. Reasonable physicists can disagree about the extent to which quantum mechanics doesn't make sense and therefore how carefully one should question and recheck a given unexpected conclusion derived from mathematics.…”
Section: B Questioning Their Conclusionmentioning
confidence: 99%
“…For example, one study found that many third-year undergraduate students interpreted quantum-mechanical uncertainty as a measure of what is unknown or limited [5]. However, a recent study found that students' epistemological views of classical and quantum mechanics are distinct [9].…”
Section: Introductionmentioning
confidence: 99%